The regular canons in the medieval British isles - Burton, Janet; Burton, Janet (Medieval church studies, 2011)
Of all the new monastic and religious groups to settle in the British Isles in the course of the twelfth century the regular canons were the most prolific. At the heart of their existence was the vita apostolica, but even more than other such groups the regular canons became involved in active spiritual care of their communities. Perhaps as a result of this feature they also enjoyed sustained support from founders, patrons and benefactors, and new foundations continued to be made long after the main force of the expansion of the monastic orders had declined. This interdisciplinary volume brings together scholars from Scotland, Ireland, Wales and England who work on aspects of the history, culture, art history and archaeology of the regular canons in the medieval British Isles